PELAKSANAAN CLEANLINESS, HEALTH, SAFETY, AND ENVIRONMENTAL SUSTAINABILITY (CHSE) DALAM RANGKA PENCEGAHAN DAN PENGENDALIAN COVID-19 DI WYNDHAM TAMANSARI JIVVA RESORT BALI - Trisdayanti, Ni Putu Eka (JURNAL BISNIS HOSPITALITI, 2023)
The tourism sector is one of the businesses affected by the Covid-19 pandemic. For the prevention and control of Covid-19, the Ministry of Tourism and Creative Economy has compiled Guidelines for the Implementation of Cleanliness, Health, Safety and Environmental Sustainability (CHSE). This study aims to determine the implementation of CHSE at Wyndham Tamansari Jivva Resort Bali. The research was conducted by conducting observations and interviews regarding the implementation of the CHSE. The data analysis technique of this research is descriptive qualitative. The results of this study are that Wyndham Tamansari Jivva Resort Bali has implemented the CHSE guidelines well, as evidenced by the existence of SOPs related to Covid-19 prevention, available hand washing areas and hand sanitizers, body temperature monitoring, use of personal protective equipment such as masks and hand gloves, area cleaning/ spraying disinfectants, special signs to keep a distance, providing food not in a buffet system. However, there are still some shortcomings that are not in accordance with CHSE guidelines, namely the use of personal protective equipment (masks, handglove) which is not consistently applied due to inconvenience and the hotel environment has begun to be poorly maintained due to efficiency in all areas such as labor, electricity and water due to the pandemic Covid-19.